Perencanaan Sistem Pengendalian Kualitas di PT. Surya Putra Barutama - Santoso, Joseph; Rahardjo, Jani (Jurnal Titra, 2014)
PT. Surya Putra Barutama is a company that produces trucks and the others heavy equipment which Dump Truck as their main product. In order to maintain the customerâs satisfaction on supplying a good quality product, the company has obtained ISO 9001:2008 in 2009. It shows the company has implemented a good quality management in accordance to the guidelines of quality standards. During the production, the company has the objective to produce a good product and having less number of defects to the product. However, the fact shows that the defect rate is still relatively high and even exceeds the standards and tolerances specified. This study aims to determine the quality planÂ for each processes by using statistical tools that are useful to control the level of defective products. The results of the Pareto diagram analysis shows that the priority defect are Over Painting (63%), Dirty Painting (60%), Uneven Paint (51%), Rough Paint (43%), Less Paint (29%), Power Take Over (53%), Porous Welding (45%), SpakBoard (39%), Less Welding (26%). The next step is to find the cause of the above defects with cause and effect diagram. It results that the cause are derived from human factors/worker, working methods, materials/raw materials and work environment. The company can take these causes into consideration on applying the Quality Plan. Quality Plan describes the quality characteristics of each process and department have standards and tolerance limits. Quality Plan also describes how the inspection and work procedures. Tub Assembly Quality Plan, SubFrame Assembly Quality Plan, Component Assembly Quality Plan, Painting Quality Plan and Finishing Quality Plan has been prepared to improve the quality planning systems and reduce the amount of re-work at the finishing stage. Preparation of Painting Quality Plan is included with the Painting Work Instructions.